Question
upstudy study bank question image url

Given the matrix \( A=\left[\begin{array}{ccc}4 & 1 & 2 \\ 1 & -6 & 3 \\ -2 & 5 & 9\end{array}\right] \) and \( B=\left[\begin{array}{ccc}2 & -3 & 4 \\ 1 & 5 & 6 \\ 8 & 2 & -7\end{array}\right] \) find \( |A+B| \)

Ask by Beck Hobbs. in Nigeria
Jan 12,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The determinant of \( A + B \) is \(-370\).

Solution

To find the determinant of \( A + B \), follow these steps: 1. **Compute \( A + B \):** Given: \[ A = \begin{bmatrix} 4 & 1 & 2 \\ 1 & -6 & 3 \\ -2 & 5 & 9 \end{bmatrix}, \quad B = \begin{bmatrix} 2 & -3 & 4 \\ 1 & 5 & 6 \\ 8 & 2 & -7 \end{bmatrix} \] Adding corresponding elements: \[ A + B = \begin{bmatrix} 4+2 & 1-3 & 2+4 \\ 1+1 & -6+5 & 3+6 \\ -2+8 & 5+2 & 9-7 \end{bmatrix} = \begin{bmatrix} 6 & -2 & 6 \\ 2 & -1 & 9 \\ 6 & 7 & 2 \end{bmatrix} \] 2. **Calculate the determinant of \( A + B \):** For a \( 3 \times 3 \) matrix: \[ \text{det} \begin{bmatrix} a & b & c \\ d & e & f \\ g & h & i \end{bmatrix} = a(ei - fh) - b(di - fg) + c(dh - eg) \] Applying this to \( A + B \): \[ \begin{aligned} \text{det}(A+B) &= 6((-1)(2) - 9 \cdot 7) \\ &\quad - (-2)(2 \cdot 2 - 9 \cdot 6) \\ &\quad + 6(2 \cdot 7 - (-1) \cdot 6) \\ &= 6(-2 - 63) + 2(-50) + 6(14 + 6) \\ &= 6(-65) - 100 + 6(20) \\ &= -390 - 100 + 120 \\ &= -370 \end{aligned} \] Therefore, the determinant of \( A + B \) is **-370**. **Answer:** \(-370\)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the determinant \( |A+B| \), we first need to compute the matrix \( A+B \). Calculating \( A + B \): \[ A + B = \begin{bmatrix} 4 & 1 & 2 \\ 1 & -6 & 3 \\ -2 & 5 & 9 \end{bmatrix} + \begin{bmatrix} 2 & -3 & 4 \\ 1 & 5 & 6 \\ 8 & 2 & -7 \end{bmatrix} \] Adding corresponding elements: \[ A + B = \begin{bmatrix} 4+2 & 1+(-3) & 2+4 \\ 1+1 & -6+5 & 3+6 \\ -2+8 & 5+2 & 9+(-7) \end{bmatrix} = \begin{bmatrix} 6 & -2 & 6 \\ 2 & -1 & 9 \\ 6 & 7 & 2 \end{bmatrix} \] Now we need to calculate the determinant \( |A+B| = | \begin{bmatrix} 6 & -2 & 6 \\ 2 & -1 & 9 \\ 6 & 7 & 2 \end{bmatrix} | \). Using the formula for the determinant of a 3x3 matrix \( |M| = a(ei-fh) - b(di-fg) + c(dh-eg) \): \[ \text{Let } M = \begin{bmatrix} a & b & c \\ d & e & f \\ g & h & i \end{bmatrix} \] Where \( a = 6, b = -2, c = 6, d = 2, e = -1, f = 9, g = 6, h = 7, i = 2 \). Now, substituting the values into the determinant formula: \[ |M| = 6((-1)(2) - (9)(7)) - (-2)(2(2) - (9)(6)) + 6(2(7) - (-1)(6)) \] Calculating each part step-by-step: 1. First term: \( 6((-2) - 63) = 6(-65) = -390 \) 2. Second term: \( -2(4 - 54) = -2(-50) = 100 \) 3. Third term: \( 6(14 + 6) = 6(20) = 120 \) Combining these: \[ |M| = -390 + 100 + 120 = -170 \] Therefore, the determinant \( |A+B| \) is: \[ \boxed{-170} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy